1999
DOI: 10.1016/s0735-1097(99)00308-3
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural quantitative coronary angiography after Palmaz-Schatz stent implantation predicts the restenosis rate at six months

Abstract: Restenosis rate after stent implantation for short lesions can be predicted using the variables percent diameter stenosis after the procedure and vessel size. This meta-analysis indicates that the concept of "the bigger the better" holds true for coronary stent implantation. Applicability of the model beyond short lesions should be tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(20 citation statements)
references
References 31 publications
1
17
0
2
Order By: Relevance
“…The factors independently associated with restenosis in our study are similar to those already described, such as reference diameter, residual stenosis after the procedure, and lesion extension [10][11][12][25][26][27][28] . We have also demonstrated that higher balloon/artery ratios and narrower vessels are associated with dissections; this finding should direct technicians to optimize the stent size, especially in patients with smaller vessels.…”
Section: Discussionsupporting
confidence: 83%
“…The factors independently associated with restenosis in our study are similar to those already described, such as reference diameter, residual stenosis after the procedure, and lesion extension [10][11][12][25][26][27][28] . We have also demonstrated that higher balloon/artery ratios and narrower vessels are associated with dissections; this finding should direct technicians to optimize the stent size, especially in patients with smaller vessels.…”
Section: Discussionsupporting
confidence: 83%
“…A combination of patient factors, such as diabetes, lesion variables including length and vessel size, and type of revascularization device, all influence the likelihood of restenosis. [1][2][3][4] With the evolution of core laboratories, such as Cardialysis in Rotterdam, large databases of clinical and angiographic data provide a unique opportunity to identify factors that may influence the restenotic process.…”
mentioning
confidence: 99%
“…This is further supported by the moderate restenosis rate after balloon dilatation alone (23.9%), and also for all lesions treated in this interventional series (18.0%). Restenosis after short stent implantation was influenced by the same variables as for other investigations, namely vessel and stent dimensions, and final luminal diameter, but not by lesion length [6, 19]. Contrary to other analyses using longer stent lengths, diabetes did not appear to influence restenosis in the short stent group [20, 21].…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, much longer stents were used than necessary to cover the target lesion in most lesions as reported in an analysis of several interventional trials using BMS [5]. Since BMS less than 10 mm in length exhibit restenosis rates between 3 and 11% in nondiabetic and 5–18% in diabetic patients, depending on the vessel diameter [6, 7], shortening the stent length might reduce the restenosis rate in BMS. We therefore conducted a prospective study to investigate in which proportion of vessels the shortest available stent could be used routinely and to determine the long-term results.…”
Section: Introductionmentioning
confidence: 99%